2020
DOI: 10.1038/s41598-020-61297-4
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-preserving distributed learning of radiomics to predict overall survival and HPV status in head and neck cancer

Abstract: A major challenge in radiomics is assembling data from multiple centers. Sharing data between hospitals is restricted by legal and ethical regulations. Distributed learning is a technique, enabling training models on multicenter data without data leaving the hospitals ("privacy-preserving" distributed learning). This study tested feasibility of distributed learning of radiomics data for prediction of two year overall survival and HPV status in head and neck cancer (HNC) patients. Pretreatment CT images were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 38 publications
(47 reference statements)
1
37
0
Order By: Relevance
“…In the perspective of personalized oncology ( 13 ) as currently implemented in the clinic, the use of quantitative imaging may allow us to overcome the known limits associated with molecular profiling. Several applications of radiomics in the field of precision radiation oncology have been identified, providing insights in terms of stage discrimination ( 14 , 15 ), molecular stratification ( 16 18 ), prognostic impact ( 19 , 20 ), and prediction of response to treatment ( 21 23 ). With imaging, the possibility to capture intrinsic tumor and organ-specific heterogeneity could be leveraged to evaluate the individual predisposition to radiation-induced toxicity ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the perspective of personalized oncology ( 13 ) as currently implemented in the clinic, the use of quantitative imaging may allow us to overcome the known limits associated with molecular profiling. Several applications of radiomics in the field of precision radiation oncology have been identified, providing insights in terms of stage discrimination ( 14 , 15 ), molecular stratification ( 16 18 ), prognostic impact ( 19 , 20 ), and prediction of response to treatment ( 21 23 ). With imaging, the possibility to capture intrinsic tumor and organ-specific heterogeneity could be leveraged to evaluate the individual predisposition to radiation-induced toxicity ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…For geometric IBMs, sphericity, volume-density and the major axis length quantified the sphericity and size of tumours. Previous studies revealed that these IBMs basically represented tumour volume, which were significantly associated with treatment outcomes [ 30 , 31 ]. In our study, the discrimination performances of the IBM nomograms were decreased when volume-related IBMs were omitted from the IBM score (C-index for the radiomics nomogram: OS, 0.672 (95% CI, 0.588–0.757); PFS, 0.629 (95% CI, 0.545–0.713) in the training cohort).…”
Section: Discussionmentioning
confidence: 99%
“…For geometric IBMs, sphericity, volume-density and the major axis length quantified the sphericity and size of tumours. Previous studies revealed that these IBMs basically represented tumour volume, which were significantly associated with treatment outcomes [30,31]. Decision curve analysis of PFS and OS were compared between the IBM score and clinical stage in the training and validation cohort, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For geometric IBMs, sphericity, volume-density and the major axis length quanti ed the sphericity and size of tumours. Previous studies revealed that these IBMs basically represented tumour volume, which were signi cantly associated with treatment outcomes [30,31]. In our study, the discrimination performances of the IBM nomograms were decreased when volume-related IBMs were omitted from the IBM score (C-index for the radiomics nomogram: OS, 0.672 (95% CI, 0.588-0.757); PFS, 0.629 (95% CI, 0.545-0.713) in the training cohort).…”
Section: Discussionmentioning
confidence: 99%